Yield loss assessment of Sclerotinia stem rot of canola in Iran - Mohammad Ali Aghajani; Naser Safaie; Azizollah Alizadeh (Journal of Crop Protection, 2013)
Sclerotinia stem rot (SSR), caused by Sclerotinia sclerotiorum, is one of the most important diseases of canola (Brassica napus) in Golestan province, the leading canola producer in Iran. In order to assess the yield loss of canola caused by SSR, 80 fields were surveyed in four different regions of the province (Gorgan, Ali Abad, Kalaleh and Gonbad) during 2006-2007, and SSR intensity was recorded weekly in the fields. Study of yield loss-SSR severity relationships by linear, nonlinear and multiple regression analyses with final intensity (Sf), time to initial symptoms (tis), Gompertz rate of disease progress (rG), and standardized area under disease progress curve (SAUDPC) as independent variables indicate that single point and integral models were significant (P < 0.05) only in three cases. Results of multiple point models which were performed using weekly recorded SSR intensities (S1, S2, …), were significant in two cases and a general model for 2007 survey was developed using S3 to S6. Eventually, response surface models were developed for each region by integrating tis with SSR intensity variables (Sf or SAUDPC).